DATA PROCESSING APPLICATIONS PAYROLL PT. PETRONUSA BUMIBAKTI USING MICROSOFT ACCESS - Untung Raharjo; Hariyanto, SKom, MMSI Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2002)
At PT. PETRONUSA BUMIBAKTI payroll data processing is still done manuallyresulting in less efficient information to employees and reports to the CEO.Therefore, in order to improve information to employees and reports to the CEO, theauthor tries to provide solutions to. PETRONUSA BUMIBAKTI order to acceleratethe processing of computerized payroll data.With existence of computerized system is expected to facilitate the time and speedinformation to employees and reports to the CEO.In this case the authors solve the problem by way of proposed procedures in theproposed system along with FOD, Diagram context, Zero Diagram, EntityRelationship Diagram, Normalization and Design File using Microsoft Access.